2018
DOI: 10.1021/acs.langmuir.8b00716
|View full text |Cite
|
Sign up to set email alerts
|

Nanometric Surface Oscillation Spectroscopy of Water-Poor Microemulsions

Abstract: Selectively exchanging metal complexes between emulsified water-poor microemulsions and concentrated solutions of mixed electrolytes is the core technology for strategic metal recycling. Nanostructuration triggered by solutes present in the organic phase is understood, but little is known about fluctuations of the microemulsion-water interface. We use here a modified version of an optoelectric device initially designed for air bubbles, in order to evidence resonant electrically induced surface waves of an oily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…However, research on dynamic phenomena in which structural self-assembly stabilizes the interface under nonequilibrium conditions is still in its infancy. This is despite the fact that in situ self-association of amphiphilic molecules has been widely observed for a variety of practical or industrial applications including oil recovery [45][46][47], flow instabilities [20,[48][49][50][51], biological systems [52][53][54], and rare metal extraction [55]. There has yet to be a fundamental study on dynamics of interfacial material formation between associating surfactants at immiscible liquid interfaces, and the connection between structure and property relationships, in addition to the underlying mechanism of structure development at the molecular level.…”
mentioning
confidence: 99%
“…However, research on dynamic phenomena in which structural self-assembly stabilizes the interface under nonequilibrium conditions is still in its infancy. This is despite the fact that in situ self-association of amphiphilic molecules has been widely observed for a variety of practical or industrial applications including oil recovery [45][46][47], flow instabilities [20,[48][49][50][51], biological systems [52][53][54], and rare metal extraction [55]. There has yet to be a fundamental study on dynamics of interfacial material formation between associating surfactants at immiscible liquid interfaces, and the connection between structure and property relationships, in addition to the underlying mechanism of structure development at the molecular level.…”
mentioning
confidence: 99%
“…Although, if in the classical extraction regime (Winsor II), we have shown in a previous paper that the chosen membrane is not a limiting factor, 33 it has recently been evidenced that liquid-liquid and liquid-solid interfaces increase the domain of stability of the liquid crystals that constitute the ''third phase''. 23 Therefore, the results concerning experiments where a third phase may be present in the pores of the membrane will have to be considered with care and with some uncertainty regarding the exact composition of the final equilibrium state.…”
Section: Discussionmentioning
confidence: 99%
“…Ion exchanges occur between aqueous (in blue) and solvent-rich phases (orange and light yellow). Kinetic barrier and asymmetry in the transfer rate are due to the thin interfacial domain, also called the interphase, 23 which is schematized as a green line. 97,98 Again, in the dilute phase, complexation versus entropy balance results in low but measurable energy of transfer.…”
Section: Effect Of Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…[29] The unusually high efficiency of TODGA is due to the formation of reverse micelles, as reviewed by Jensen et al [30] The interphase existing at the water/diluent interface has also been observed and studied in details recently by Nanometric Surface Oscillation Spectroscopy. [31] Varying the pH was also presenting a great interest beyond membrane characterization because obtaining efficiency in hydrometallurgy processes at high pH is the subject of intense research, as it enable to reduce process cost and the amount of effluent to be treated. [32] Validation of microfluidic membrane extraction results was performed by comparison to results obtained by batch extraction experiments.…”
Section: Experimental Methodsmentioning
confidence: 99%